Proposta de eficiência energética para a escola técnica SENAI de Ribas do Rio Pardo - MS - Pangoni, Fabricio; Riccio Barbosa, Andrea Teresa (Latin American Journal of Energy Research, 2023)
This article proposes a reduction in energy consumption and financial calculations with the replacement of air conditioners for the SENAI technical school in Ribas do Rio Pardo / MS. For this purpose, were made consumption calculations, cooling calculation analysis and demand. For the financial calculation, a one-year projection was used for energy consumption for low voltage in the convencional energy plan and, for medium voltage in the tarifa horaria verde, according to the energy values of the energy concessionaire Energisa MS, which the institution is connected. Finally, the economic feasibility of this project was carried out, with the values of Payback, Net Present Value (NPV) and Internal Rate of Return (IRR). The results show electrical energy savings, this project would be viable in less than 1 year Keywords: Air conditioner, consumption calculation, technical analysis, energy efficiency.